Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, dan Kecerdasan Spiritual Pemilik pada Kinerja UMKM di Kabupaten Gianyar - Laras Witrisanti Bayu, Ni Luh; Sukartha, I Made (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
The performance of Micro, Small and Medium Enterprises needs to be investigated because the export value of MSME is considered to continue to increase by touching 19.9 MSME is 61.41%, while in employment of MSME dominates 97% of the total national workforce. This study aims to determine the influence of intellectual intelligence, emotional intelligence, and spiritual intelligence of the owner on the performance of Micro, Small and Medium Enterprises. The object of the research is the performance of MSME in Gianyar Regency. The sampling technique used in this study is Probably sampling used by using a simple random technique. There are 100 MSME as a sample with 71 statements. Based on the results of the research analysis, Intellectual Intelligence has a positive effect on MSME Performance, Emotional Intelligence has a positive effect on MSME Performance, and Spiritual Intelligence has a positive effect on MSME Performance. Keyword s: Intellectual intelligence, emotional intelligence, spiritual intelligence